Post-ERCP Dormia basket impaction: a case report and literature review - Sedik, Alaaeldin Mohamed; Hussein, Abrar; Alshimary, Abdelmajid; Elsayed, Mostafa; Alzayed, Ahmed; Alharbi, Nada (International Surgery Journal, 2021)
The incidence of Common bile duct stones (CBD) in patients undergoing cholecystectomy is 10%. The present-day management of common bile duct stone may be pre-, intra-, or post-operative Endoscopic retrograde cholangio-pancreatography (ERCP) with stone extraction. The reported complications of ERCP and CBD stone extraction range from 5 to 10% cases, that might be life threatening. Herein, we reported a case of calculus obstructive jaundice and cholangitis. Unfortunately, trials for ERCP and stone retrieval was followed by impacted Dormia basket which was successfully managed by surgerys.